2017
DOI: 10.1089/aid.2017.0009
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status and Kidney Function Decline in HIV-Infected Men: A Longitudinal Study in the Multicenter AIDS Cohort Study

Abstract: Vitamin D may play an important role in a range of disease processes. In the general population, lower vitamin D levels have been associated with kidney dysfunction. HIV-infected populations have a higher risk of chronic kidney disease. Few studies have examined the link between lower vitamin D levels and kidney function decline among HIV-infected persons. We investigated the associations of serum 25-hydroxyvitamin D [25(OH)D] and 1,25-dihydroxyvitamin D [1,25(OH)D] with kidney function decline in a cohort of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
5
1
Order By: Relevance
“…Interestingly, as in the Mendelian randomization study by Teumer et al, there was an inverse relationship found between 25(OH)D levels and eGFR; the higher the 25(OH)D levels, the lower the eGFR. This is in contrast to other longitudinal studies where low 25(OH)D levels at one time point are associated with a faster decline in eGFR (9,18).…”
Section: (Oh)d Levels and Renal Hyperfiltration Incontrasting
confidence: 99%
See 1 more Smart Citation
“…Interestingly, as in the Mendelian randomization study by Teumer et al, there was an inverse relationship found between 25(OH)D levels and eGFR; the higher the 25(OH)D levels, the lower the eGFR. This is in contrast to other longitudinal studies where low 25(OH)D levels at one time point are associated with a faster decline in eGFR (9,18).…”
Section: (Oh)d Levels and Renal Hyperfiltration Incontrasting
confidence: 99%
“…Ravani et al showed that serum 25(OH)D was an independent inverse predictor of kidney disease progression and death in 168 patients with early stages of CKD (8). In a cohort of men with HIV infection, lower 25(OH)D levels were associated with a faster decline in eGFR (18). Randomized clinical trials and a meta-analysis have shown that treatment with vitamin D analogs may decrease proteinuria in diabetic nephropathy and other proteinuric diseases (19,20).…”
Section: Vitamin D Levels and Kidney Diseasementioning
confidence: 99%
“…In HIV-positive patients, reduced vitamin D concentrations were often found at various levels of severity and have been linked to low bone-mineral density and related disorders, subclinical vascular disease, kidney function decline, endocrine disorders, liver fibrosis, preterm delivery and neurocognitive impairment [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…However, younger black Americans who have higher eGFR than white American in their cohort did not prove this association. Regarding serum 1, 25 (OH) 2 D, both showed with rapid decline of eGFR but not statistically significant 7 .Their findings were also contradictory to the fact of faster eGFR decline among racial difference of black individuals 5,6 . Their findings might be due to the distribution of age and eGFR across their cohort 7,20 .…”
Section: Overall Participant Characteristicsmentioning
confidence: 74%
“…[4][5][6] However, for HIV population, it had been proved only in few western cohorts with several limitations in the context. 6,7 Then, more new studies are required for HIV populations of different regions world-wide to prove this finding universally.…”
Section: Field Of Study: Clinical Sciencesmentioning
confidence: 99%